Factors associated with depression, anxiety, and stress among medical college students - Phuong, Nguyen Viet; Thong, Nguyen Quang; Ve, Pham Van; Hieu, Vo Thi; Tu, Le Thi Cam; Tha, Le Kim; Hang, Tran Thi Thuy (Tạp chí Nghiên cứu Y học, 2024)
Academic pressure, stress, and associated factors are pervasive throughout education. Lately, depression, anxiety, and stress emerged as alarming mental health issues among health science students. A cross-sectional descriptive study was conducted among 2,064 students at Can Tho Medical College to determine the prevalence of depression, anxiety, and stress, along with associated factors. Data were collected online using the DASS-21 questionnaire via Google Forms. The prevalence rates of depression, anxiety, and stress among college students were 52.4%, 73.1%, and 58.8%, respectively. Factors associated with these conditions included gender, body satisfaction, daily smartphone use, primary smartphone activities, satisfaction with academic performance, ease of forming friendships, and presence of close friends. As depression, anxiety, and stress were significant concerns among medical college students, educators should implement screening programs and develop strategies to improve and enhance students’ mental health.